2001
DOI: 10.1038/sj.cgt.7700337
|View full text |Cite
|
Sign up to set email alerts
|

Single-chain antibody-mediated gene delivery into ErbB2-positive human breast cancer cells

Abstract: Targeted gene transfer by nonviral vectors can be achieved through incorporation of specific ligand( s ) into the vectors. In this study, the effects of incorporation of an anti -ErbB2 single -chain antibody fragment ( ScFv ) into nonviral vectors for targeted gene delivery were investigated. The ML39 ScFv, selected from a human ScFv phage display library and affinity matured in vitro ( K d =1Â10 À 9 M ), was used as ligand specific for the extracellular domain of the tumor surface protein, ErbB2. Two approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…In the past few years, several groups have developed antibodies, scFV fragments, and peptides [7][8][9][10] that bind to EGFR-2.…”
mentioning
confidence: 99%
“…In the past few years, several groups have developed antibodies, scFV fragments, and peptides [7][8][9][10] that bind to EGFR-2.…”
mentioning
confidence: 99%
“…This antibody-mediated uptake has been successfully used to deliver plasmid DNA and antisense oligonucleotides. [13][14][15][16][17] Recently, Song et al 18 demonstrated that siRNA targeted delivered to human immunodeficiency virus-infected cells and HER2 positive cells by this strategy executed gene silencing. However, whether this promising strategy for siRNA delivery is applicable to other diseases remains unknown.…”
mentioning
confidence: 99%
“…1). In contrast, the previous study reported the selective delivery of ML39 ScFv complexed with DNAs into HER2/ neu-positive cells (Li et al, 2001). It seems likely that the association of cells with ML39 ScFv-presenting bacteria is not sufficient to trigger the receptor-mediated entry mechanism.…”
Section: Discussionmentioning
confidence: 76%